No Evidence That Siblings' Gender Affects Personality across Nine Countries - Thomas Dudek; Anne Ardila Brenøe; Jan Feld; Julia Rohrer (Institute of Labor Economics (IZA), 2022)
Does growing up with a sister rather than a brother affect personality? In this paper, we provide a comprehensive analysis of the effects of siblings' gender on adults' personality, using data from 85,887 people from 12 large representative surveys covering 9 countries (the United States, the United Kingdom, the Netherlands, Germany, Switzerland, Australia, Mexico, China, and Indonesia). We investigated the personality traits risk tolerance, trust, patience, locus of control, and the Big Five. We found no meaningful causal effects of the gender of the next younger sibling, and no associations with the gender of the next older sibling. Based on high statistical power and consistent results in the overall sample and relevant subsamples, our results suggest that siblings' gender does not systematically affect personality.
Keywords: J12; J16; J24; 330; personality; economic preferences; sibling gender; sibling sex